Economic Dispatch of Grid-Connected Microgrid for Smart Building Considering the Impact of Air Temperature - Mohamad Abou Houran; Wenjie Chen; Minghui Zhu; Liyu Dai (IEEE Access, 2019)
The economic dispatch (ED) operation is based on determining the optimal output of all the distributed energy resources (DERs) of a microgrid to meet the load demand at the lowest cost. In this paper, a smart commercial building model is supplied by several distributed generations (DGs), for example, PV power plants, diesel generators, and energy storage system (ESS). In addition, the microgrid is connected to the main grid (grid-connected mode), which allows the system to trade power with the main grid. The aim of this paper is managing DERs that operate over a time horizon and satisfy several key constraints at the lowest possible cost. Therefore, an improved energy management (EM) operation is proposed to achieve better energy efficiency in the building. In the proposed EM operation, the ED problem is investigated according to several aspects, such as the impact of air temperature, thermal resistance (R) of the building envelope, and time horizon (day-ahead ED and five-minute-ahead ED). Finally, the results of the general algebraic modeling system (GAMS) are used to validate the accuracy and feasibility of the proposed EM operation.